2019
DOI: 10.1002/pts.2483
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alginate and zein films as a carrier of natamycin to increase the shelf life of kashar cheese

Abstract: The aim of this study was to develop alginate and zein films containing natamycin, a natural antifungal agent, in order to limit/prevent the mould growth on the surface of kashar cheeses. The films were prepared by casting, and characterized in terms of antimicrobial and mechanical properties (tensile strength, elongation‐at‐break, and elastic modulus), and their morphology was examined by scanning electron microscopy (SEM). Mechanical properties of the zein films were found to be weaker than the alginate film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…This packaging may contain an antimicrobial agent incorporated in a polymeric matrix, which is released gradually or slowly to retard or avoid the natural deterioration of food by microorganisms and foodborne diseases. 7,10,11 Essential oils (EOs) are known as one of the natural antimicrobial agents, consisting of a mixture of volatile lipophilic constituents extracted from different plants, such as thyme, rosemary, sage, clove bud, oregano and cinnamon, among others. [12][13][14] In their constitution they have functional groups with hydrophilic character (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This packaging may contain an antimicrobial agent incorporated in a polymeric matrix, which is released gradually or slowly to retard or avoid the natural deterioration of food by microorganisms and foodborne diseases. 7,10,11 Essential oils (EOs) are known as one of the natural antimicrobial agents, consisting of a mixture of volatile lipophilic constituents extracted from different plants, such as thyme, rosemary, sage, clove bud, oregano and cinnamon, among others. [12][13][14] In their constitution they have functional groups with hydrophilic character (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This effect could change food packaging conditions and extend the packaging shelf life. This packaging may contain an antimicrobial agent incorporated in a polymeric matrix, which is released gradually or slowly to retard or avoid the natural deterioration of food by microorganisms and foodborne diseases 7,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Hager, Rawles, Xiong, Newman, and Webster (2019) reported that nisin contained in an edible coating (90,000 IU/15 ml film solution) based on corn‐zein has proven to be an effective bacteriocin against L. monocytogenes inoculated on the surface of a covered fish fillets (counts greater than 7 log in the non‐antimicrobial systems vs. 1 log counts in the nisin system on the fifth day of storage). Küçük, Çelik, Mazi, and Türe (2020) evaluated alginate and zein films as a carrier of natamycin in order to limit/prevent the mold growth on the surface of kashar cheeses. The authors concluded that the films with high‐natamycin concentrations showed higher antifungal activity (against Aspergillus niger and Penicillium camemberti ) for 45 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Alginate and corresponding derivatives are one of the most promising carbohydrates for packaging applications, especially for foods that are sensitive to gas permeation [222]. Alginates are naturally occurring indigestible polysaccharides.…”
Section: Alginatesmentioning
confidence: 99%